OBSERVATION AND GIVING FEEDBACK - Muhammadjonova Nurjaxon Ulug’bek qizi, (ZAMONAVIY TA'LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2025)
Effective teaching in English as a Foreign Language (EFL) classrooms relies heavily on continuous professional development, where observation and feedback play a central role. This study investigates how classroom observation, combined with systematic and reflective feedback, can enhance the pedagogical skills of pre-service teachers. Specifically, it examines how various types of feedback—oral vs. written, immediate vs. delayed, and peer vs. mentor feedback—impact teaching performance, classroom management, and learner engagement.